2011
DOI: 10.1063/1.3556742
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dissipation elements in a fully developed turbulent channel flow by tomographic particle-image velocimetry

Abstract: A new method to describe statistical information from passive scalar fields has been proposed by Wang and Peters ͓"The length-scale distribution function of the distance between extremal points in passive scalar turbulence," J. Fluid Mech. 554, 457 ͑2006͔͒. They used direct numerical simulations ͑DNS͒ of homogeneous shear flow to introduce the innovative concept. This novel method determines the local minimum and maximum points of the fluctuating scalar field via gradient trajectories, starting from every grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Previous PIV and laser Doppler velocimetry measurements showed that the flow inside the measurement section is two-dimensional and fully turbulent. Tomographic PIV measurements have successfully been applied to investigate turbulent flow structures such as dissipation elements [31].…”
Section: Methodsmentioning
confidence: 99%
“…Previous PIV and laser Doppler velocimetry measurements showed that the flow inside the measurement section is two-dimensional and fully turbulent. Tomographic PIV measurements have successfully been applied to investigate turbulent flow structures such as dissipation elements [31].…”
Section: Methodsmentioning
confidence: 99%
“…An important characteristic of the statistics of the separation length , is its invariance toward changes in Reynolds numbers when normalized with the mean length , Ã ¼ ,=, m Schaefer et al, 2011;Gampert et al, 2013a). The probability density functions (PDF) of the normalized separation length Pð,=, m Þ are shown in Figure 4 for all cases both in linear and linear logarithmic scale.…”
Section: Marginal Statistics Dissipation Element Parametermentioning
confidence: 99%
“…For example, dissipation elements were used to understand the scales of scalar structures in DNS of homogeneous shear turbulence [WP06, WP08], to measure the turbulence scales as a function of distance from a wall structure in a wall‐bounded fluid flow [AO11], to partition a DNS of temporally evolving shear layer into laminar, turbulence interface, and turbulent regions [MWP09], and to apply the same zonal partitioning and statistics to experimental data collected using high‐speed Laser‐Rayleigh scattering imaging [GSNP13]. Recently, Schaefer et al [SDKS11] computed dissipation elements for the first time on experimental data of a fully developed turbulent channel flow using tomographic particle‐imagery velocimetry. Schaefer et al [SGP12] have extended the concept of dissipation elements to velocity fields to study flow‐inherent properties.…”
Section: Related Workmentioning
confidence: 99%